Performance of garden pea (Pisum sativum L.) genotypes for growth and yield characters at Dailekh, Karnali Province, Nepal - Luitel, Binod Prasad; Bhandari, Bishnu Bahadur (Nepal Agriculture Research Journal, 2023)
Fourteen garden pea genotypes (13 improved genotypes and 1 was standard released variety) were evaluated for their morpho-agronomic characters, powdery mildew (PM) disease resistant, and yield performance. The genotypes were evaluated in randomized complete block design with three replications at Horticulture Research Station (HRS), Dailekh in 2018 and 2019. The results revealed that genotypes were significantly (P<0.01) different for pod length (cm), pod diameter (mm), green pod plant-1 (no.), green pod weight plant-1 (g), seed pod-1 (no.), dry pod plant-1 (no.), dry seed weight plant-1 (g), hundred seed weight (g) and seed yield (mt ha-1) except days to 50% flowering, plant height (cm) and branch/plant (no.). Green pod weight was significantly (P<0.01) higher in genotypes HRSDGP-11-18-10 (233.1 g plant-1) and HRSDGP-11-18-1 (224.1 g plant-1) than Sikkim Local (198.3 g/plant). Genotypes HRSDGP-11-18-10, HRSDGP-11-18-13 and HRSDGP-11-18-1 showed moderate resistant (3.0) reaction to PM disease. Green pod weight plant-1 showed significant (P<0.01) positive correlation with seed number/plant (r=0.74**), dry pod number/plant (r=0.52**), dry seed weight (r=0.58**) and seed yield (r=0.57**). Genotypes HRSDGP-11-18-10, HRSDGP-11-18-1 and HRSDGP-11-18-13 showed 32.3%, 20.5% and 2.9% seed yield advantage over the standard variety, Sikkim Local. Based on this result, HRSDGP-11-18-10, HRSDGP-11-18-1 and HRSDGP-11-18-13 are selected as high yielding and PM resistant genotypes which can be used for commercial production as well as breeding lines for garden pea improvement program.